Interpretasi Ayat-ayat Pernikahan Wanita Muslimah dengan Pria Non Muslim Perspektif Rasyid Ridha dan Al-Maraghi - Desri Ari Enghariano (Institut Agama Islam Negeri Padangsidimpuan, 2020)
Lately, cases of interfaith marriage have occured in many communities and it has caused a stir. Whats else is marriage between muslimah and non muslim men, this case caused controversy among muslims community. Among the commentators who were concerned about this problem were Rasyid Ridha and al-Maraghi. Therefore, this study will discuss their interpretation of the verses of marriage between muslimah and musyrik men and ahli kitab men. This study uses a comparative method. The results showed that the problem of marriage between muslimah and musyrik men, Rasyid Ridha only based on the surah al-Baqarah verse 221 in the establishing the law. While al-Maraghi strengthened it with surah al-Mumtahanah verse 10. In terms of methodolgy, they both adhere to the itthlaq al-lafzhi approach. Then the problem of marriage between mulimah and ahli kitab men, Rasyid Ridha was less strict in expressing his interpretation of the prohibition. While al-Maraghi is more assertive and cleare. In the terms of methodology, the adhere to the mafhum al-mukhalafah approach. Their interpretation of the marriage between muslimah and musyrik men and ahli kitab men is still relevant today.